2012
DOI: 10.1021/jf302007v
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering Ability of Phytate toward Biologically and Environmentally Relevant Trivalent Metal Cations

Abstract: Quantitative parameters for the interactions between phytate (Phy) and Al(3+), Fe(3+), and Cr(3+) were determined potentiometrically in NaNO(3) aqueous solutions at I = 0.10 mol L(-1) and T = 298.15 K. Different complex species were found in a wide pH range. The various species are partially protonated, depending on the pH in which they are formed, and are indicated with the general formula MH(q)Phy (with 0 ≤ q ≤ 6). In all cases, the stability of the FeH(q)Phy species is several log K units higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…This is in good agreement with the work of Bretti et al [21] and Torres et al [24], who both potentiometrically determined different partially protonated iron(III) phytate species, indicated with general formula [FeH i L] z-(with 0 ≤ i ≤ 6 and 2 ≤ i ≤ 5, respectively). Iron phytate species written in the reactions (12-13) below were predicted on the basis of the latter, hence the most protonated (less stable) species being [FeH 5 L] 4-.…”
Section: Electrochemical Characterization Of Iron-phytate System On Hmdesupporting
confidence: 92%
See 3 more Smart Citations
“…This is in good agreement with the work of Bretti et al [21] and Torres et al [24], who both potentiometrically determined different partially protonated iron(III) phytate species, indicated with general formula [FeH i L] z-(with 0 ≤ i ≤ 6 and 2 ≤ i ≤ 5, respectively). Iron phytate species written in the reactions (12-13) below were predicted on the basis of the latter, hence the most protonated (less stable) species being [FeH 5 L] 4-.…”
Section: Electrochemical Characterization Of Iron-phytate System On Hmdesupporting
confidence: 92%
“…Fe(II) phytates were investigated by many authors [9,20,21,24,47]. Torres et al [24] reported that the highest protonation degree of iron(III) phytate species formed in acidic media is i = 5 and log of the stability constant …”
Section: Iron(iii) Solution Equilibriamentioning
confidence: 99%
See 2 more Smart Citations
“…39 Phytates interact strongly also with iron(III) ions and play an important role in biologically-relevant processes as described in numerous papers. 8,35,[40][41][42][43][44] Complexation of iron(III) ions with phytate show different behavior than alkaline or alkaline earth cations. Three distinct EPs are detected on titration curves of phytic acid in the presence of various amounts of Fe 3+ ions (Fig.…”
Section: +mentioning
confidence: 99%